Determinants of audit quality: A study of auditors at the supreme audit agency of the Republic of Indonesia - Nadhilah Riswina Hilda; Marfuah, Marfuah; Tarmizi, Masetah Ahmad (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2026)
The purpose of this study was to examine the influence of competence, work experience, independence, professional skepticism, self-efficacy, and professional ethics on audit quality among auditors at the Supreme Audit Agency of the Republic of Indonesia (BPK RI) Representative Office of the Special Region of Yogyakarta. The study population was all 51 auditors working at the BPK RI Representative Office of the Special Region of Yogyakarta. The sample consisted of 41 active auditors working at the BPK RI Representative Office of the Special Region of Yogyakarta, selected using a purposive sampling technique. The results of this study provide evidence that the competency variable has a significant positive effect on audit quality. Meanwhile, work experience, independence, professional skepticism, self-efficacy, and professional ethics do not significantly influence audit quality. The results of this study are expected to contribute to the BPK RI institution's efforts to improve audit quality, one of which is by improving auditor competence in accordance with applicable standards.